2019
DOI: 10.1007/978-3-030-19135-1_9
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Clinical Task Interruptions on Subsequent Performance of a Medication Pre-Administration Task

Abstract: There is a surge of research exploring the role of task interruptions in the manifestation of primary task errors both in controlled experimental settings, and safety critical workplaces such as healthcare. Despite such research providing valuable insights into the disruptive properties of task interruption, and, the importance of considering the likely disruptive consequences of clinical task interruptions in healthcare environments, there is an urgent need for an approach that best mimics complex working env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…An experimental study which mimicked a real clinical setting related with medication preparation tasks demonstrated a significant difference between conditions with and without interruptions. The likelihood of errors increased as the complexity of the conditions increased from low to moderate to high, while no errors were committed under the no‐interruption conditions (Williams et al, 2020). An Australian study demonstrated a significant positive association ( p = 0.01) between the presence of interruptions and the rate of medication errors in a real clinical setting.…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study which mimicked a real clinical setting related with medication preparation tasks demonstrated a significant difference between conditions with and without interruptions. The likelihood of errors increased as the complexity of the conditions increased from low to moderate to high, while no errors were committed under the no‐interruption conditions (Williams et al, 2020). An Australian study demonstrated a significant positive association ( p = 0.01) between the presence of interruptions and the rate of medication errors in a real clinical setting.…”
Section: Introductionmentioning
confidence: 99%